2019
DOI: 10.1007/978-3-030-18293-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design of Information Sharing Tools for Disaster Risk Reduction

Abstract: Disaster information sharing tools are an important aspect of disaster resilience, and it is of utmost importance that these tools are accessible and usable for as many potential users as possible. In this paper, we evaluate the accessibility of a selection of tools for crowdsourcing disaster situation information. As our evaluation shows that the selected tools are not fully accessible, we provide recommendations for mitigation, as well as highlight the importance of further research in this area. With today'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…When the digital volunteers are primarily working through digital platforms, the usability and accessibility of these platforms are very important. However, the awareness of the importance of these factors among experts in ICT for emergency management is relatively low [38,39].…”
Section: Accessibility Of Tools and Platforms For Dhvsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the digital volunteers are primarily working through digital platforms, the usability and accessibility of these platforms are very important. However, the awareness of the importance of these factors among experts in ICT for emergency management is relatively low [38,39].…”
Section: Accessibility Of Tools and Platforms For Dhvsmentioning
confidence: 99%
“…Some success criteria can be automatically tested and others require human evaluation. In the previous study, automatic evaluation of a selection of typical web-based tools and platforms for crowdsourcing of information for DHVs have revealed that the tools and platforms tested are not accessible [39]. The main page as well as volunteer signup or information submission pages were tested as these typically are the first potential barriers (issues potentially blocking users from accessing some or all of the information or functionality of the web site) for new volunteers.…”
Section: Accessibility Of Tools and Platforms For Dhvsmentioning
confidence: 99%
“…Although Information sharing and crowdsourcing tools has become a hot topic recently, the importance of these is also increasing as people are more and more using mobile tools for communication. These tools are therefore still number two on our Research Agenda increasingly important in disaster resilience, and it is essential that these tools are accessible and usable for as many potential users as possible, both from the general public and active volunteers (Radianti et al 2017;Radianti and Gjøsaeter 2019). This should have a high priority as these tools are affecting many users and their ability to report the situation in their area.…”
Section: Tools/technologies In Emergency Managementmentioning
confidence: 99%
“…To mention two examples: A selection of web-based tools and platforms for crowdsourcing of information for enhanced public resilience were examined. The results show that none of the tested tools were universally designed and accessible to all users (Radianti et al 2017). A study of a set of emergency alert sign-up pages in the northeast of US showed that of 26 webpages that were evaluated, 21 had accessibility issues (Wentz et al 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation